Modeling option and strategy choices with connectionist networks: towards an integrative model of automatic and deliberate decision making - Andreas Glöckner; Tilmann Betsch (Max Planck Institute for Research on Collective Goods, 2008)
We claim that understanding human decisions requires that both automatic and deliberate processes be considered. First, we sketch the qualitative differences between two hypothetical processing systems, an automatic and a deliberate system. Second, we show the potential that connectionism offers for modeling processes of decision making and discuss some empirical evidence. Specifically, we posit that the integration of information and the application of a selection rule are governed by the automatic system. The deliberate system is assumed to be responsible for information search, inferences and the modification of the network that the automatic processes act on. Third, we critically evaluate the multiple-strategy approach to decision making. We introduce the basic assumption of an integrative approach stating that individuals apply an all-purpose rule for decisions but use different strategies for information search. Fourth, we develop a connectionist framework that explains the interaction between automatic and deliberate processes and is able to account for choices both at the option and at the strategy level.
Keywords: 330; System 1; Intuition; Reasoning; Control; Routines; Connectionist Model; Parallel Constraint Satisfaction; Entscheidung; Kognition; Verhaltensökonomik; Theorie